The Total Artificial Heart in End-Stage Congenital Heart Disease - Villa, Chet R.; Morales, David L. S. (Frontiers in Physiology, 2017)
The development of durable ventricular assist devices (VADs) has improved mortality rates and quality of life in patients with end stage heart failure. While the use of VADs has increased dramatically in recent years, there is limited experience with VAD implantation in patients with complex congenital heart disease (CHD), despite the fact that the number of patients with end stage congenital heart disease has grown due to improvements in surgical and medical care. VAD use has been limited in patients with congenital heart disease and end stage heart failure due to anatomic (systemic right ventricle, single ventricle, surgically altered anatomy, valve dysfunction, etc.) and physiologic constraints (diastolic dysfunction). The total artificial heart (TAH), which has right and left sided pumps that can be arranged in a variety of orientations, can accommodate the anatomic variation present in CHD patients. This review provides an overview of the potential use of the TAH in patients with CHD.